SHOULD INJURY PREVENTION STRATEGIES BE INTRODUCED INTO PHYSICAL EDUCATION LESSONS AT SCHOOL? (Fiep Bulletin - online, 2014)
Asymmetries in muscle strength exceeding 15% between the two lower-limbs are considered potential causative factors ofinjury. The objective of the study was to determine the percentages of strength asymmetry between the lower-limbs of school children andinvestigate whether values >15% correlated with performance in speed drills. The sample was composed of N=138 students (72 M and66 F, 12.0±1.1 yrs; 52.4±11.1 Kg, 159±0.08 cm) attending the first 3 years of an Italian middle school. Lower-limb strength asymmetrieswere assessed using the tests: One-Leg Hop (OLH ), One-Leg Triple Hop (OLTH ) and Side Hop (SH ); running speed was assessed usingthe tests: 10 and 20m sprint, 10x5m Shuttle Sprint and 4.115m Side Steps and Forward (4.115m SSF ). To test for correlations betweenlower-limb asymmetries and running speed performance, Pearson’s correlations were calculated. Statistical significance was consideredfor p15%.Pearson’s correlations revealed that values of asymmetry >15% in the OLH and OLTH tests positively correlate with performance inthe shuttle test (r=0.452, N=23; p
Keywords: Strength asymmetry; Injury Prevention; School; Children